Need to bring family to the heart of healthcare as it is home, not a hospital, where healthcare begins and ends - Sanjiv Kumar; Pankaj Bhardwaj; Neeta Kumar (Indian Journal of Community Medicine, 2023)
Today the patients and their families are 'powerless' recipients of healthcare services. The healthcare services are siloed and fragmented and getting worse with an increasing array of specialists and subspecialists who “patch up” patients and send them back home. It is important for healthcare providers to become involved in the process of health promotion, prevention, and recovery. For successful implementation of this family-level care needs to be recognized and integrated into all policies, guidelines of the government, and healthcare providers reoriented through in-service and basic training.